Religious Framing and Social Identity in Religion-Based Political Communication at Local Election - Ginting, Abdul Fikri; Azhar, Anang Anas; Efendi, Erwan (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines how religion-based political communication is constructed, disseminated, and interpreted in the Regional Head Election (Pilkada) of North Padang Lawas Regency, a region characterized by strong religious authority and dense religious networks. Moving beyond descriptive accounts, this research offers an analytical contribution by demonstrating how religious symbols, narratives, and actors operate simultaneously as framing devices, sources of social identity, and instruments of political legitimacy within local electoral contestation. Employing a qualitative political communication approach, data were collected through in-depth interviews with key religious institutions—Majelis Ulama Indonesia (MUI), Nahdlatul Ulama (NU), Muhammadiyah, and Al Washliyah—supported by document analysis and campaign material review. The findings reveal three main patterns: (1) religious narratives are strategically framed to construct candidates’ moral legitimacy; (2) religious leaders and networks function as opinion leaders who translate political messages into normative religious values; and (3) hybrid communication patterns combining face-to-face religious forums and digital media amplify emotional resonance while narrowing spaces for critical political deliberation. The integration of framing theory and social identity theory demonstrates that religion-based communication not only mobilizes voter participation but also shapes collective political preferences grounded in socio-religious identity rather than programmatic evaluation. North Padang Lawas serves as a critical case illustrating how local religious authority intensifies both the effectiveness and ethical risks of religion-based political communication. This study contributes to political communication scholarship by highlighting the dual role of religion as a mobilizing resource and a potential source of social polarization, offering implications for ethical campaign practices and the preservation of social cohesion in local democracies.